The Way of Discipleship : Women, Men, and Today's Call to Mission - Gittins, Anthony J., 1943- (Book collections on Project MUSE., 2016)
In The Way of Discipleship, theologian Anthony Gittins describes the eternal mission of the Trinity, historically brought "down to earth" in the ministry of Jesus, and then continued to the ends of the earth by those called and sent as disciples throughout future generations. Gittins explains that Christian discipleship must be the living out of Jesus' own example in many different times and places. He encourages people of all ages to follow the invitation of Jesus to be missionary disciples. The Way of Discipleship explores several New Testament examples of Jesus' call and commissioning, distills the principles involved, and then recontextualizes the stories so that they pose a direct challenge to disciples today. In this way, Gittins builds up a picture both of "the Way" of Jesus himself, and of the way in which today's disciples can loyally follow his call to mission.